Kepatuhan Menelan Obat Penderita Tuberculosis di Puskesmas Seulimeum Aceh Besar - Andi Zulhaida; Rosdiana Rosdiana; Veny Wilya (Poltekkes Kemenkes Maluku, 2020)
Tuberculosis (Tb) still a major health problem in developing countries. The success of reducing Tb disease is influenced by compliance behavior and regularity in disease control. The study aims to identify factors related to medication adherence Tb patients. The study is cross sectional design. Data were collected using a questionnaire conducted in 2016. Determination of sample using a total population technique that is 36 Tb patients who consume OAT (Anti Tuberculosis Medication). The results of the study of 10 Tb patients having good Drug Consumption Supervisor (PMO) 76,9%, 14 Tb patients having good family roles 73,7% and 17 good transportation facilities 70.8% to the level of medication adherence was good. There is a relationship between PMO (p-value=0.014), transportation facilities (p-value=0.001), and family roles (p-value=0.001) with medication adherence Tb patients and there is no relationship between drug availability (p-value=0.281) with medication adherence Tb patients. Medication adherence Tb patients is associated with PMO, drug availability, transportation facilities, and family roles. Tb patients are expected to be consistent to take medication regularly and thoroughly.